The Challenge of Treatment in Bipolar Depression: Evidence from Clinical Guidelines, Treatment Recommendations and Complex Treatment Situations - Köhler, S.; Gaus, S.; Bschor, T. (Pharmacopsychiatry, 2014)
Bipolar depression and its clinical presentation is a frequent but complex psychiatric disease. Despite the high prevalence and the clinical and economic relevance of bipolar depression, few treatments are proven to be highly and consistently effective. In practice, the treatment of bipolar depression typically includes complex treatment decision-making. The best evidence for a pharmacological treatment exists for quetiapine. Alternatives with limitations are lamotrigine (also in the combination with lithium), carbamazepine and olanzapine. The effectiveness and recommendation of antidepressants in the treatment of bipolar depression remains controversial. Initially, depressive episodes should been treated with one of the named substances with antidepressant properties. In non-responders, a combination of lithium and lamotrigine, or antidepressants in combination with either lithium, an antiepileptic drug or atypical antipsychotics, may be necessary. If a depressive episode occurs under ongoing mood-stabilizing treatment, combination treatments of different substances, even with antidepressants, can be necessary. In the case of treatment-resistant depressive episodes, complex treatment strategies (combination therapies, MAO inhibitors) should be considered. This review describes the treatment recommendations of different guidelines for bipolar depression and emphasizes their differences. Furthermore, alternative pharmacological treatment strategies and complex treatment situations are discussed.
Keywords: bipolar disorder treatment; depression treatment; mood disorders